P93 Outcomes of enhanced triage of rheumatology referrals at a single point of access. (20th April 2020) - Forgie, Bethan; Garrood, Toby
Abstract: Background: With increasing pressure on rheumatology services there is a need to identify alternative pathways for patients which are better aligned to their needs. East Surrey CCG is formed of 17 GP practices serving an adult population of 137, 000. First Community Health and Care acts as a single point of referral for patients with musculoskeletal conditions. In 2018 a triage service was established, run by a GP with an extended role (GPweR), for patients referred to rheumatology. Analysis of triaged patients was undertaken to explore the feasibility of diverting a subgroup of patients with non-inflammatory conditions into community-based care. Methods: Referrals from February 2018 to March 2019 were analysed from the point of triage to confirmation of the diagnosis in secondary care. Triage was undertaken with additional reference to the primary care record in EMIS. For each referral it was recorded whether, according to the available information, this was more likely to be an inflammatory or non-inflammatory condition and whether they could have been seen first in a community GPwER rheumatology clinic. The final diagnosis after their hospital appointment was recorded. A pilot GPweR-led community clinic was established in April 2019 to see those patients selected by the process as suitable for community-based care. Results: 407 patients were triaged. 96% were triaged to secondary care. Of these, records from the subsequent rheumatology appointment(s) were available for 312. The final diagnosis was inflammatory in 120 (38%) and non-inflammatory in 192 (62%). 152 patients (49%) were thought to have a non-inflammatory condition at triage which was confirmed in 83% of cases after a consultant appointment. 160 patients (51%) were thought likely to have an inflammatory condition which was confirmed in 59%. Positive predictive value of the triage process for non-inflammatory conditions was 83%, negative predictive value 59%, sensitivity 66%, specificity 79%. 57 patients selected from triage were seen in the pilot community clinic. Final diagnoses were: 53% fibromyalgia, 19% osteoarthritis, 12% soft tissue rheumatism, 14% gout/inflammatory arthritis. 54% of patients needed blood tests and 39% imaging. 31% required a face to face follow up appointment and 47% were referred to physiotherapy. 7% were referred on to rheumatology. Conclusion: Referrals to secondary care rheumatology are rising and putting increasing pressure on services and referral to treatment times. There is a need to develop alternative pathways for patients with non-inflammatory conditions who could be managed in community settings. Our work shows that a majority of these can be identified at the point of triage with good specificity. We have also shown that of those seen in a pilot community clinic few needed onward referral. Our work suggests that there is a substantial opportunity to develop alternative and potentially more cost-effective community-based pathways for patients. Disclosures: B. Forgie None. T. Garrood None.